2007
DOI: 10.1007/s11064-007-9451-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electro-acupuncture on PDGF Expression in Spared Dorsal Root Ganglion and Associated Dorsal Horn Subjected to Partial Dorsal Root Ganglionectomy in Cats

Abstract: The effects of electro-acupuncture (EA) on the expression of platelet derived growth factor (PDGF) in spared dorsal root ganglion (DRG) and associated dorsal horns were evaluated in cats subjected to bilateral removal of L1-L5 and L7-S2 DRG, while sparing L6 DRG and were demonstrated using Immunohistochemistry, Western blot and RT-PCR techniques. On the acupunctured side, there was a significant increase in the total number of PDGF positive neurons. Large neurons of the L6 DRG at 7 days post operation (dpo), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Muitas destas pesquisas foram úteis, mas são muito discutíveis do ponto vista ético (40)(41)(42)(43)(44)(45)(46) . Em gatas submetidas à ovariohisterectomia (OH), a EA em E36 e vesícula biliar (VB) 34 diminuiu o consumo de anestésico e promoveu estabilidade cardiorrespiratória, sendo superior à AP falsa sem EA (47) e ao uso da morfina (48) .…”
Section: Resultsunclassified
“…Muitas destas pesquisas foram úteis, mas são muito discutíveis do ponto vista ético (40)(41)(42)(43)(44)(45)(46) . Em gatas submetidas à ovariohisterectomia (OH), a EA em E36 e vesícula biliar (VB) 34 diminuiu o consumo de anestésico e promoveu estabilidade cardiorrespiratória, sendo superior à AP falsa sem EA (47) e ao uso da morfina (48) .…”
Section: Resultsunclassified
“…[23] Based on the model of growth control system, minor perturbations such as acupuncture around the singular points of the growth control system can be beneficial as disease modifying therapy in treating many inflammatory and degenerative disorders beyond symptom relief. Acupuncture has been shown to regulate bone morphogenetic protein, retinoic acid [84], wnt, nerve growth factor, [85,86] IGF-1 [87,87,88] , platelet derived growth factor [89], atrogin-1, protein kinase Akt1, [70] vascular endothelial growth factor, angiogenesis, [90] increase bone density [91,91,92], neuroplasticity (as in the healing of spinal cord injury) [87], and stem cell proliferation. [93] , [69] Acupuncture showed promise in ameliorating muscle atrophy, [70] osteoporosis [94] , [91] obesity [95], diabetes [96], polycystic ovary syndrome [86], stroke [90], and sepsis [97,98].…”
Section: The Singularity and The Utility Of The Organizer Networkmentioning
confidence: 99%
“…To ensure unbiased and accurate representation of the data, 5 sections of each tissue block were taken randomly from all consecutive sections, representing all the samples in one animal. The sections were then processed for IHC as described before [9], using rabbit polyclonal IGF-I antiserum (Santa Cruz, 1:200), biotinylated goat anti-rabbit immunoglobulin G (IgG, dilution 1:200) and avidin-biotin-peroxidase complex (ABC) (Vector Stain Elite Kit, Vector Laboratory, Burlingame, CA, USA). For the control of immunostaining specificity, the primary antibody was omitted and the IGF-I antibody, pre-adsorbed with IGF-I.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Recent studies have also demonstrated the presence of some neurochemicals in the spinal cord associated with EA treatment of cats subjected to partial dorsal root ganglionectomies [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%